Sexual antagonism leads to a mosaic of X‐autosome conflict. (11th January 2020) - Frank, Steven A.; Patten, Manus M.
Abstract: Males and females have different optimal values for some traits, such as body size. When the same genes control these traits in both sexes, selection pushes in opposite directions in males and females. Alleles at autosomal loci spend equal amounts of time in males and females, suggesting that the sexually antagonistic selective forces may approximately balance between the opposing optima. Frank and Crespi noted that alleles on the X chromosome spend twice as much time in diploid females as in haploid males. That distinction between the sexes may tend to favor X‐linked genes that push more strongly toward the female optimum than the male optimum. The female bias of X‐linked genes opposes the intermediate optimum of autosomal genes, potentially creating a difference between the direction of selection on traits favored by X chromosomes and autosomes. Patten has recently argued that explicit genetic assumptions about dominance and the relative magnitude of allelic effects may lead X‐linked genes to favor the male rather than the female optimum, contradicting Frank and Crespi. This article combines the insights of those prior analyses into a new, more general theory. We find some parameter combinations for X‐linked loci that favor a female bias and other parameter combinations that favor a male bias. We conclude that the X likely contains a mosaic pattern of loci that differ with autosomes over sexually antagonistic traits. The overall tendency for a female or male bias on the X depends on prior assumptions about the distribution of key parameters across X‐linked loci. Those parameters include the dominance coefficient and the way in which ploidy influences the magnitude of allelic effects.